2012
DOI: 10.1016/j.virol.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type coxsackievirus infection dramatically alters the abundance, heterogeneity, and immunostimulatory capacity of conventional dendritic cells in vivo

Abstract: In vitro studies have shown that enteroviruses employ strategies that may impair the ability of DCs to trigger T cell immunity, but it is unclear how these viruses affect DCs in vivo. Here, we evaluate the effects of wild-type (wt) coxsackievirus B3 on DCs in vitro and in a murine model in vivo. Although CVB3 does not productively infect the vast majority of DCs, virus infection profoundly reduces splenic conventional DCs numbers and diminishes their capacity to prime naïve CD8+ T cells in vitro. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…We have not yet elucidated the immune mechanisms responsible for viral clearance from the heart in our juvenile mouse model. However, the limited CD3 staining in the heart observed at 2 and 77 days is consistent with previous studies demonstrating a lack of functional antiviral T cells following CVB3 infection [40], [41], and suggests that the type I interferon response may ultimately be responsible for controlling the viral infection [42]. We observed that after CVB3 exposure in vivo , CPCs showed a strong tendency to differentiate into vascular cells.…”
Section: Discussionsupporting
confidence: 92%
“…We have not yet elucidated the immune mechanisms responsible for viral clearance from the heart in our juvenile mouse model. However, the limited CD3 staining in the heart observed at 2 and 77 days is consistent with previous studies demonstrating a lack of functional antiviral T cells following CVB3 infection [40], [41], and suggests that the type I interferon response may ultimately be responsible for controlling the viral infection [42]. We observed that after CVB3 exposure in vivo , CPCs showed a strong tendency to differentiate into vascular cells.…”
Section: Discussionsupporting
confidence: 92%
“…As previously described (3, 18) small (~5mg) pieces of spleen were harvested and stored in RNA later (Qiagen). RNA was isolated using RNeasy mini (Qiagen) with on-column DNA digestion according to manufacturer instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction conditions were as follows: 25°C for 10 min, 48°C for 30 min, and 95°C for 5 min. Real time PCR was performed as described (10) using Taqman Universal PCR master mix (Applied Biosystems) with the following primers and probe: Forward primer (900nM) 5′-CGCTGGCCTGGGTGAAT-3′, Reverse primer (900nM) 5′-ATGGGAAAACACAACAATTGATCTC-3′ (Valuegene), and probe (200nM) 6FAM-CTGCAGGTTTCTCGC-MGBNFQ (Applied Biosystems). Reaction conditions were: 95°C for 10 min and 40 cycles of 95°C for 15 sec and 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%